Tindak Tutur Imperatif Dialog Talk Show TV One News Episode “Tindakan Asusila, Motif Pembunuhan Brigadir Joshua” - Warda, Firda; Anshari, Anshari; Usman, Usman (Nuances of Indonesian Language, 2025)
This research aims to (1) describe the imperative form of dialogue in the TV One News talk show episode "Immoral Actions, Motive for the Murder of Brigadier Joshua". (2) describe the meaning of the imperative in the TV One News talk show dialogue episode "immoral act as the motive for the murder of Brigadier Joshua.". The research method used is a qualitative approach, with a focus on data analysis in the form of words, phrases and imperative sentences contained in the talk show. The research results show two things, firstly, two forms of imperatives are identified, namely a structural imperative form and a non-structural imperative form. These two studies describe the nine meanings of imperatives, namely commands, requests, persilaa, requests for permission, prohibitions, hopes, suggestions, invitations and threats.